1973
DOI: 10.1111/j.1476-5381.1973.tb08246.x
|View full text |Cite
|
Sign up to set email alerts
|

The oestrous cycle and monoamine oxidase activity

Abstract: Summary1. During the oestrous cycle of the rat, monoamine oxidase (MAO) activity was studied in the uterus, the ovaries and the adrenal glands and also in 4 brain regions which are rich in monoamines. In all these structures the activity was lowest during the night between oestrus and metoestrus. High values were found in di-oestrus, with the exception of the uterus in which the MAO activity reached its peak during metoestrus. 2. A stimulating effect of progesterone on uterine, ovarian and adrenal MAO activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…MAO in placenta plays a great role in the maintenance of pregnancy, and the placenta of patients with complications such as toxemia, diabetes mellitus, and hydatidiform mole have a low MAO activity (Yoshimoto et al 1986a). It was reported that during the rat estrous cycle, MAO activity of brain, uterus and ovary is changed corresponding to the alteration of sex steroid concentration (Holzbauer and Youdin 1973;Yoshimoto et al 1986b). However, the details of MAO activity in rat organs, such as liver, uterus, fetal liver and placenta during pregnancy still remains to be clarified.…”
mentioning
confidence: 99%
“…MAO in placenta plays a great role in the maintenance of pregnancy, and the placenta of patients with complications such as toxemia, diabetes mellitus, and hydatidiform mole have a low MAO activity (Yoshimoto et al 1986a). It was reported that during the rat estrous cycle, MAO activity of brain, uterus and ovary is changed corresponding to the alteration of sex steroid concentration (Holzbauer and Youdin 1973;Yoshimoto et al 1986b). However, the details of MAO activity in rat organs, such as liver, uterus, fetal liver and placenta during pregnancy still remains to be clarified.…”
mentioning
confidence: 99%
“…A specific regulatory system may exist to control rat placental MAO. This would not be unique because hormonal regulation of MAO activity in several rat organs has been reported (Holtzbauer & Youdim, 1973). Koren, Pfeifer & Sulman (1965) reported a gradual increase of serotonin and a gradual decrease of MAO in human placenta during pregnancy.…”
mentioning
confidence: 99%
“…We chose this particular regimen of treatment with exogenous steroids not specifically to mimic natural cyclic changes but to be able to compare our results with those of Holzbauer & Youdim (1973) (Youdim & Holzbauer, 1976). For instance, kynuramine metabolism was increased two-fold whereas 5-HT metabolism was unchanged with progesterone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1.4.3.4). In several tissues known to be under the influence of ovarian hormones (uterus, ovary, endometrium), MAO activity is affected by changes in endogenous steroid level during menstrual (Southgate, Grant, Pollard, Pryse-Davies & Sandler, 1968) and oestrous (Holzbauer & Youdim, 1973) cycles or by treatment with exogenous steroids (Collins, Pryse-Davies, Sandler & Southgate, 1970). The lung has a large capacity to metabolize 5-HT via the action of MAO but the effect of ovarian steroids on this activity has not been investigated.…”
Section: Introductionmentioning
confidence: 99%